Towards controlled polymer brushes via a self-assembly-assisted-grafting-to approach - Tian Zhou (Nature Portfolio, 2016)
Polymer brushes, whereby single layers of polymers are tethered to surfaces, can be made by various methods but greater control over their fabrication is desirable. Here, by pre-assembling polymer chains into 2D crystalline sheets, the authors achieve high precision and unprecedented grafting densities.